Assessment of arboviruses circulation in wild rodents and birds in the Upper Paraná Atlantic Forest - Brividoro, Melina Victoria (2022)
Arboviruses are transmitted by hematophagous arthropods, many of them of sanitary importance for their impact on health, economy and their wide geographic distribution. In the sylvatic cycle, different wild vectors and hosts are involved. Some of these viruses belong to the Flavivirus and Alphavirus genera and are transmitted by different species of mosquitoes. Several wild vertebrates participate in the sylvatic cycles of these viruses as main or alternative hosts. Our aim was to evaluate the circulation of Flavivirus and Alphavirus genera in the Upper Paraná Atlantic Forest (UPAF) of Misiones, Argentina.